Energy Transition, Green Growth and Emission on Economic Growth using Spline Approach: Evidence from Asia-Pasific Countries - Idris Aditya; Razak Abd Rahman (ECONOMICS)
This study examines the impact of energy transition, green growth, and emissions on economic growth across 36 Asia-Pacific countries using the spline approach. By utilizing cross-sectional data from 2022 and 2023, the research explores the nonlinear relationships between these variables and provides insights into achieving sustainable economic growth. The results show that countries with an Energy Transition Index below 47.02 can achieve a 0.41% increase in economic growth, while those within the range of 47.02 to 54.44 experience a higher growth potential of 0.67%. However, countries with an index exceeding 65.71 see a slightly lower growth rate of 0.59%, indicating that advanced transitions require more targeted strategies to sustain economic performance. Similarly, the Green Growth Index exhibits a nonlinear effect. Countries with an index below 43.19 show a 0.16% increase in economic growth, but those within the 43.19 to 53.82 range face a 0.13% decline in potential growth. Notably, countries with very high green growth scores above 65.75 manage to reverse the trend and achieve a modest 0.04% growth. In contrast, emissions have a predominantly negative impact. Countries with emissions below 265.53 MtCO2e still manage a 0.01% growth, but those with emissions exceeding 522.51 MtCO2e face a decline in economic growth of up to 0.10%. This study provides actionable insights for policymakers to develop tailored strategies that promote renewable energy investments, green innovations, and emissions reductions to achieve sustainable economic growth in the Asia-Pacific region.. The study emphasizes the need for tailored strategies that focus on renewable energy investments, green innovation, and emission reductions to achieve sustainable economic development. By adopting spline regression models, this research offers new insights for policymakers to develop data-driven strategies that enhance economic growth while promoting green transitions in the Asia-Pacific region.